The Runaway Bride - Chukwuemeka, Ernest (Evans Brothers [Nigeria Publishers] Limited, 2012)
The Runaway Bride is a play which narrates the ordeals of young teenage girls given out in early marriage.
Keywords: Drama; Early Marriage; Nigeria